Climate change adaptation in the Canadian wine industry: Strategies and drivers. (16th December 2020) - Jobin Poirier, Emilie; Plummer, Ryan; Pickering, Gary
Abstract : The wine industry is and will continue to be impacted by climate change. The adaptation of vineyards and winery practices is therefore paramount to the success of winegrowing operations around the globe. We surveyed winegrowers across Canada to assess their adaptation status, the strategies they currently use or plan to implement to cope with the effects of climate change, and the drivers that influence the adoption of adaptation measures. We found that Canadian winegrowers are most adapted to weather events associated with precipitation and drought and less adapted to other extreme weather events. Our results also show that winegrowers' concern about climate change exerts a small, but significant, positive effect on both climate change adaptation and the willingness to adapt in the future. Moreover, winegrowers with smaller operations are less likely to be adapted to some weather events associated with climate change. This research provides an overview of the state of climate change adaptation by winegrowers in Canada and supports the implementation of context‐specific adaptations in wine regions throughout the country. Key Messages: This is the first examination of current and planned responses to climate change by Canadian winegrowers. Canadian winegrowers are more adapted to rainfall‐related weather events, but less adapted to extreme events, such as consecutive hot days and freeze‐thaw cycles. Context‐specific adaptations in Canadian wine regions are important. L'adaptation de l'industrie viticole canadienne aux changements climatiques : les stratégies et facteurs d'influence: L'industrie viticole est affectée par les changements climatiques et elle continuera de l'être dans les années à venir. L'adaptation des vignobles et des pratiques viticoles est donc primordiale pour le succès des exploitations viticoles dans le monde entier. Au cours de cette recherche, nous avons interrogé des viticulteurs à travers le Canada pour évaluer leur état d'adaptation, les stratégies qu'ils utilisent actuellement ou auxquelles ils prévoient faire appel pour faire face aux effets des changements climatiques, ainsi que les facteurs qui influencent l'adoption de mesures d'adaptation. Nous avons constaté que les viticulteurs canadiens se sont bien adaptés aux événements météorologiques associés aux précipitations et à la sécheresse, contrairement aux autres événements météorologiques extrêmes. Nos résultats montrent également que l'inquiétude des viticulteurs face aux changements climatiques exerce un effet positif, faible, mais significatif, à la fois sur l'adaptation aux changements climatiques et sur la volonté de s'adapter dans l'avenir. De plus, il est moins probable que les viticulteurs ayant des exploitations plus petites soient susceptibles de s'adapter à certains événements météorologiques liés aux changements climatiques. En somme, cette recherche donne un aperçu de l'état de l'adaptation des viticulteurs aux changements climatiques au Canada et elle soutient l'utilisation d'adaptations spécifiques selon le contexte dans les différentes régions viticoles du pays.